Effectiveness of Professional Skills Development Program (PSDP) on Job-seeker skills in terms of different Skill seminars, department and gender - Rahman, Sadia (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.